Drug Discovery for Overcoming Chronic Kidney Disease (CKD): Prolyl-Hydroxylase Inhibitors to Activate Hypoxia-Inducible Factor (HIF) as a Novel Therapeutic Approach in CKD - Tetsuhiro Tanaka; Masaomi Nangaku (Elsevier, 2009)
Hypoxia-inducible factor (HIF) is a heterodimeric transcription factor composed of an oxygen-dependent α-subunit and constitutively expressed β subunit, which plays a central role in cellular adaptation to hypoxia by transcriptionally upregulating its target genes involved in angiogenesis, erythropoiesis, glycolysis, and so on. Recent studies demonstrated that hypoxia in the tubulointerstitium is involved in the pathology of progressive renal diseases and that HIF, which is activated in experimental kidney diseases, may serve to protect tubulointerstitium from the ischemic insult. The expression of HIF α-chains is post-translationally regulated and hydroxylation at one or two of the conserved proline residues by prolyl-hydroxylase domains (PHDs) is a critical step for the oxygen-dependent recruitment of the von Hippel-Lindau gene product (pVHL), a recognition component of the E3 ubiquitin ligase complex, and degradation of HIF-α. Conversely, modalities to inhibit the enzymatic activities of PHDs have been shown to activate HIF irrespective of oxygenation status and are regarded as candidate targets of pharmacological approaches against chronic kidney diseases characterized by hypoxia. Keywords:: chronic kidney disease (CKD), hypoxia-inducible factor (HIF), prolyl-hydroxylase domain (PHD)